Effect of 1-methylcyclopropene (1-MCP) treatment on firmness and softening related enzymes of ‘Sekaki’ papaya fruit during ripening at ambient - Azhane Ahmad,; Zainon Mohd Ali,; Zamri Zainal, (Universiti Kebangsaan Malaysia, 2013)
1-Methylcyclopropene (1-MCP) has been found to inhibit ethylene action and thus it can delay the fruit ripening process. The effects of 1-MCP (90 ppb for 12 h) on softening related changes were determined through physiological changes, fruit firmness and activities of the cell wall degrading enzymes including α-galactosidase, β-galactosidase, pectin methylesterase (PME) and xylanase during ripening in papaya (Carica papaya L. cv Sekaki). In this study, fruits were treated with 90 ppb concentration of 1-MCP gaseous vapors for 12 h in airtight container maintained at 28oC. After the treatment fruits were placed at ambient temperature (28oC). Papaya treated with 1-MCP experienced a significant delayed in skin color development, weight loss and reduced firmness loss compared with the fruit without 1-MCP treatment. As softening progressed, activity of the cell wall degrading enzymes in fruit without 1-MCP treatment increased significantly coincident with a rapid decline in fruit firmness. With 1-MCP application, fruit experienced a delay in activity of cell wall degrading enzymes but continued to increase until later stage of ripening. Thus it may be suggested that 1-MCP treatment may aid in delaying softening-related process and thereby extended the postharvest life and maintained the quality of the ‘Sekaki’ papaya fruit.